The Differences in Characteristics of Fruit Leather from Custard Apple with Variations in Hydrocolloid Types and Cooking Time - Maulida, Syifa Nur; Umiyati, Rini; Muflihati, Iffah (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Custard apple has a short shelf life, so they need processing to extend their shelf life, one of which is processed into fruit leather products. The purpose of this study was to determine the influence of different types of hydrocolloids and cooking time on the physical, chemical, and sensory characteristics. This study used a Complete Random Design (RAL) using two treatment factors, including the addition of variations in hydrocolloid types (pectin, carrageenan, and carboxyl methylcellulose (CMC)) and cooking time (3, 5, and 10 minutes), each treatment is repeated 3 times. The results of the study had a real influence on physical and chemical characteristics, with the best treatment results reviewed from the values of L*79.1, a* 4.9 and b* 15, tensile strength 2.86 Mpa, pH 4.32, total dissolved solids 30.3 °Brix, moisture content 22.55%, ash content 5.55%, vitamin C 24.22 mg/100 grams, total sugar 54.54% and antioxidant activity 58%.